Controlled-Release Dispenser and Dry Trap Developments for Drosophila suzukii Detection - Larson, Nicholas R.; Strickland, Jaime; Shields, Vonnie D. C.; Zhang, Aijun (Frontiers in Ecology and Evolution, 2020)
The spotted wing drosophila (SWD), Drosophila suzukii, is an exotic vinegar fly originating from South-East Asia and has invaded many American and European countries. This devastating pest has caused severe damage on soft-skinned fruit crops, which has resulted in large economic losses. Although many D. suzukii detection devices have been developed and used by growers/farmers in orchards, most of them did not meet their expectation. More simple, convenient, and efficient detection tools are still urgently needed so that growers/farmers can make timely management decision. In our previous study a quinary blend, containing acetoin, as a long-range, and ethyl octanoate, as a short-range attractant for SWD, had been identified. In this study, a controlled-release polyethylene dispenser containing five identified attractants: acetoin, ethyl octanoate, ethyl acetate, penethyl alcohol, and acetic acid, was tested in laboratory conditions for release rates, as well as in a blueberry field and an adjacent wooded area for trapping activity. Release of the most D. suzukii attractants from the polyethylene dispenser was constant. In the laboratory, release rates of ethyl acetate (0.3 g/day over 14 days), phenethyl alcohol (0.0054 g/day over 36 days), and acetic acid (0.13 g/day over 36 days) followed zero order kinetics. Acetoin and ethyl octanoate were blended together and had a varied release rate. In the field, dry and liquid traps baited with the optimized controlled-release dispenser were evaluated and compared with liquid traps baited with apple cider vinegar (ACV). During blueberry harvest season in 2018, the liquid traps containing drowning solution baited with the optimized controlled-release dispenser caught both male and female D. suzukii two weeks earlier and had significantly higher selectivity than that of ACV traps in the field. Additionally, in 2019 field tests, dry traps baited with the controlled-release dispenser demonstrated earlier detection compared to the ACV traps. Due to the simplicity of the dry trap design and easy processing, it has great potential to be an efficient and convenient D. suzukii detection tool for growers/farmers.